2012
DOI: 10.1038/onc.2012.270
|View full text |Cite|
|
Sign up to set email alerts
|

p16INK4A Represses the paracrine tumor-promoting effects of breast stromal fibroblasts

Abstract: Cancer-associated fibroblasts (CAFs), the most abundant and probably the most active cellular component of breast cancer-associated stroma, promote carcinogenesis through paracrine effects; however, the molecular basis remains elusive. We have shown here that p16INK4A expression is reduced in 83% CAFs as compared with their normal adjacent counterparts cancer-free tissues isolated from the same patients. This decrease is mainly due to AUF1-dependent higher turnover of the CDKN2A mRNA in CAFs. Importantly, p16I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 41 publications
4
66
0
Order By: Relevance
“…This corroborates our recent findings showing that most human cancer-associated fibroblasts have reduced levels of p16 and that specific p16 downregulation increases the expression of ␣-SMA and SDF-1 and activates breast stromal fibroblasts (28). Similar findings were reported for p53 and p21 (29,(42)(43)(44), indicating that downregulation of these tumor suppressor genes is an important step toward the activation of stromal fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This corroborates our recent findings showing that most human cancer-associated fibroblasts have reduced levels of p16 and that specific p16 downregulation increases the expression of ␣-SMA and SDF-1 and activates breast stromal fibroblasts (28). Similar findings were reported for p53 and p21 (29,(42)(43)(44), indicating that downregulation of these tumor suppressor genes is an important step toward the activation of stromal fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
“…(hereafter referred to as p16) is reduced in active cancer-associated fibroblasts and that p16 down-regulation plays a major role in the activation of breast stromal fibroblasts (28). In the present report, we sought to determine the molecules and pathways that underlie the paracrine effects of breast cancer cells on stromal fibroblasts, leading to their activation and the downregulation of p16, p21, and p53.…”
Section: Ink4amentioning
confidence: 98%
“…mCAFs, especially those isolated from the interface zone of breast tumors, are claimed to be a robust inducer of EMT [94,95]. With respect to the molecular mechanism, many mediators, such as Twist1 [96], SDF-1 [97] and the SNAIL family [51], were identified. Cycloxygenase-2 (COX-2)/nuclear factor-kappa B (NFκB)/hypoxiainducible factor-1 (HIF-1) signaling, and TGFβ, ERK, JUN and RHO signaling are thought to be responsible for mCAF-induced EMT [68,94,95,[98][99][100].…”
Section: Mcafs Drive Cancer Cell Migration Invasion and Metastasismentioning
confidence: 99%
“…Furthermore, p16 has antiinflammatory functions in rheumatoid synovial fibroblasts in vitro (44,45). Moreover, we have recently shown that p16 represses the expression/secretion of IL-6 in breast stromal fibroblasts (10).…”
Section: Obesity Activates Breast Adipocytesmentioning
confidence: 95%
“…In breast stromal fibroblasts, it has been shown that tumor suppressor genes, such as p16 INK4A (p16), play major roles in repressing the expression/secretion of several cancer-promoting cytokines (10).…”
mentioning
confidence: 99%